Model Tes Kebugaran Pelajar Nusantara (TKPN) Bagi Siswa SMP Kristen 2 Mollo Utara - Mae, Ramona Mathias; Palinata, Yahya Jecson; Baun, Alventur; Leko, Julian Jeminel (Jurnal Media Informatika, 2024)
Physical fitness is a mirror of the ability to function systems in the body that can realize an improved quality of life in physical activity. Through developing physical fitness, children will be guaranteed in their readiness to carry out their daily activities in the school environment and at home. To be able to measure the physical fitness of each person, it can use the Harvad Step Test, Cooper, ACSPFT (Asia Committee on the Standardization of Physical Fitness Test), TKJI (Indonesian Physical Fitness Test), TKPN (Nusantara Student Fitness Test) and so on. Therefore, the purpose of this study is the Student Fitness Test Nusantara (TKPN) model which will be used to measure the physical fitness level of Christian Junior High School 2 Mollo Utara students. The method used in this research is descriptive quantitative. Data collection techniques involve tests and measurements using the Student Fitness Test Nusantara (TKPN) norms for students aged 9-18 years. Body Mass Index (BMI) results for male and female students are in the normal nutritional status category, V-Sit and Reach and Sit Up results for male and female students are in the good category, Squat Thrust and Pacer Test results for male and female students are in the sufficient category. The results of the Nusantara Student Fitness Test (TKPN) for Christian Junior High School 2 Mollo Utara students show that student fitness must be improved through regular, programmed and systematic exercise activities.